Raman Spectroscopy: Can it change the future of Brain Tumour Surgery? - Qurat-Ul-Ain Virani; Hafiza Fatima Aziz; Shahzad Shamim (Journal of the Pakistan Medical Association, 2023)
Raman Spectroscopy (RS) is one of several techniques being used to identify tumour tissue during brain surgery. It is emerging as a novel investigative and diagnostic tool. The application of RS in cancer treatment has displayed promising results. This review centers around its clinical implication in brain tumours. Keywords: Raman spectroscopy, brain tumour, neurosurgery